The analysis of interlingual and intralingual grammatical errors due to first language interference among diploma students - Nasrudin, Nasiha; Mohd Akhir, Nurhafeza; Aziz, Muhammad Nasiruddin (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
This study seeks to identify the errors in writing made by Malay ESL students that can be attributed to mother tongue interference. The content analysis of 29 academic compositions in the form of expository essays written by UiTM Puncak Perdana diploma students was conducted. Students were required to produce 250- 300 word essays on the effects of procrastination on students within an hour and a half without using any outside resources, such as dictionaries or class notes. The mean word count of the 29 compositions was 305. Based on the findings, it can be said that the reason why the students made the errors was due to inter and intralingual mistakes. This paper presents and discusses a descriptive analysis of the results with respect to three main types of interference: the use of singular and plural nouns, subject-verb agreement, and the copula 'be'.